Cloud observability in action - Hausenblas, Michael (Manning Publications, 2024)
Cloud Observability in Action gives you the background and techniques you need to successfully introduce observability into cloud-based serverless and Kubernetes environments. In it, you'll learn to use open standards and tools like OpenTelemetry, Prometheus, and Grafana to build your own observability system and end reliance on proprietary software. You'll discover insights from different telemetry signals, including logs, metrics, traces, and profiles. Plus, the book's rigorous cost-benefit analysis ensures you're getting a real return on your observability investment.
Online resource; title from title details screen (O'Reilly, viewed March 19, 2024)
Keywords: Cloud computing; Observers (Control theory); Observabilité (Théorie de la commande); Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet